Acoustic microscopy - Briggs, Andrew (Oxford University Press, 2010)
For many years 'Acoustic Microscopy' has been the definitive book on the subject. A key development since it was first published has been the development of ultrasonic force microscopy. This edition has a major new chapter on this technique and its applications.
Keywords: Materials -- Microscopy.; Acoustic microscopy.; elektronické knihy; electronic books